⇒ x2 - 5x + 2x - 10 = 0
⇒ x(x - 5) + 2(x - 5) = 0
⇒ (x + 2) (x - 5) = 0
The roots of the equation are those value for which (x + 2) (x - 5) = 0
⇒ x = - 2 or 5
- 2 and 5 are the roots of the given equation.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :